A comparative research on teachers’ knowledge in five Asia-Pacific countries in the COVID-19 pandemic: The case of tourism and hospitality education - Chen, Yen-Jung; Hsu, Liwei (Frontiers in Education, 2022)
The COVID-19 outbreak at the beginning of 2020 has drastically impacted almost every aspect of our daily life. Empirical evidence is lacking on which sector of knowledge in technology-enhanced teaching needs to be developed further for tourism and hospitality programs conducted online. The present study investigated teachers’ technology, learners, pedagogy, academic discipline content knowledge, and context knowledge (TLPACK) in tourism and hospitality online education settings using comparative research methods. A total of 173 participants from five countries (Indonesia, Philippines, Taiwan, Thailand, and Vietnam) were surveyed online. The results revealed that, despite the fact that they were from different countries, all teachers reached a consensus that their knowledge about learners was the lowest during the online teaching period of the pandemic; meanwhile, they all ranked academic knowledge as the highest among these five variables except Vietnamese teachers who considered their knowledge on pedagogy to be the highest. Additionally, their TLPACK revealed significant differences in various countries and differences in academic discipline content knowledge are caused by the interaction of nationality and gender. This study overcomes a major limitation of previous studies on how the pandemic has affected educational praxis as the focus of previous research has been on the situation in a single country. Therefore, the present study’s findings can serve as a reference for practitioners of tourism and hospitality online education in Asia-Pacific region when facing unprecedented and urgent changes of educational practices during and post the COVID-19 pandemic.